Polyethyleneimine is a potent systemic adjuvant for glycoprotein antigens. (20th May 2014) - Sheppard, Neil C.; Brinckmann, Sarah A.; Gartlan, Kate H.; Puthia, Manoj; Svanborg, Catharina; Krashias, George; Eisenbarth, Stephanie C.; Flavell, Richard A.; Sattentau, Quentin J.; Wegmann, Frank
Abstract : PEI induces robust adjuvant effects when delivered systemically Abstract: Polyethyleneimine (PEI) is an organic polycation used extensively as a gene and DNA vaccine delivery reagent. Although the DNA targeting activity of PEI is well documented, its immune activating activity is not. We recently reported that PEI has robust mucosal adjuvanticity when administered intranasally with glycoprotein antigens. Here, we show that PEI has strong immune activating activity after systemic delivery. PEI administered subcutaneously with viral glycoprotein (HIV-1 gp140) enhanced antigen-specific serum IgG production in the context of mixed Th 1/Th 2-type immunity. PEI elicited higher titers of both antigen binding and neutralizing antibodies than alum in mice and rabbits and induced an increased proportion of antibodies reactive with native antigen. In an intraperitoneal model, PEI recruited neutrophils followed by monocytes to the site of administration and enhanced antigen uptake by antigen-presenting cells. The Th bias was modulated by PEI activation of the Nlrp3 inflammasome; however its global adjuvanticity was unchanged in Nlrp3-deficient mice. When coformulated with CpG oligodeoxynucleotides, PEI adjuvant potency was synergistically increased and biased toward a Th 1-type immune profile. Taken together, these data support the use of PEI as a versatile systemic adjuvant platform with particular utility for induction of secondary structure-reactive antibodies against glycoprotein antigens.